Helia (De Gruyter, 2000)
HELIA publishes original theoretical, experimental and technical contributions arising from the scientific study of sunflower crops and farming systems. Scientific Journal HELIA is published by the Serbian Academy of Sciences and Arts (SASA), Branch in Novi Sad in cooperation with De Gruyter.